Unraveling the Uncertainty of the Niger Delta Crisis through Taxation - Ngerebo-A, Tamunonimim A (Asian Economic and Financial Review, 2013)
This paper critically x-rayed the known causes, consequences and two out of the numerous solutions to the Niger Delta Crisis (NDC). The two solutions implemented by governments in Nigeria in tackling the Niger Delta Crisis are the military option and the amnesty option. It adopted the ethnographic descriptive research methodology, given that the researcher interacted with some of the members of some agitating groups as well as administering questionnaire and interview a cross section of the residents of the region. The paper found that these two solutions implemented so far have recorded minimal or transient successes, and therefore concludes that the poor performance is attributable to the conflicting expectations of the various tiers of government, the people of the region and the agitating groups. It therefore recommends a more comprehensive solution to the crisis, christened Tax Option, which has the policy implication of unraveling the uncertainty surrounding the crisis, reconciles the various expectations and satisfying them.